Pengobatan Alternatif Bekam Kering terhadap Kadar Kolesterol Darah - Syokumawena Syokumawena; Marta Pastari (Jurnal Keperawatan Silampari, 2021)
This study aimed to determine the effectiveness of dry cupping alternative treatment on blood cholesterol levels. The research method in this study used a pre-experimental design with a two-group pre-and post-test design. The results showed that most of the blood cholesterol levels before cupping were nine people (30.0%) with worrying blood cholesterol levels (200-239). Most of the blood cholesterol levels before 13-point cupping were 11 people (36.7%) with High Blood Cholesterol Levels (>240), then after 13-point cupping, 11 people (36.7%) had Worrying Blood Cholesterol Levels (200-239). In conclusion, groups 9 and 13 cupping points affect reducing blood cholesterol levels. Keywords: Cupping, Cholesterol, Alternative Medicine